Multiple wavelength Brillouin fiber laser from injection of intense signal light - Harun, Sulaiman Wadi; Shirazi, Mohammadreza Rezazadeh; Ahmad, Harith (John Wiley & Sons, 2013)
A multiple wavelength Brillouine fiber laser (BFL) is demonstrated using an injection of intense light at 1480 nm. The light generates Raman gain at around 1560 nm to amplify the Brillouin-Rayleigh backscattered light in the medium and allows the generation of multiple lines by self-feedback-seeding effects. Three Stokes are obtrained in the BFL with the maximum power of the first Stokes at approximately -6 dBm from the injection of 1780 nm light at 150 mW. The line spacing is measured to be approximaltely 0.08 nm. There is no significant change in the power of the first Stokes with the injection of 1480 nm light; however the powers of additional Stokes are highest at Brillouin pump of 1560 nm.